Possible biogeochemical response to the passage of Hurricane Fabian observed by satellites - Son, S; Platt, T; Fuentes-Yaco, C; Bouman, H; Devred, E; Wu, Y; Sathyendranath, S (2007)
Physical and biogeochemical changes induced by the Hurricane Fabian in the Northwest Atlantic in early September 2003 were observed using composite satellite images. After the passage of the hurricane, the mean sea surface temperature (SST) along the track decreased on average by about 1.3°C with maximum decrease of 10°C. At the same time, the mean Chl a concentration increased by about 42%. Entrainment of cold, nutrient-rich waters by vertical mixing induced by the hurricane seems to have enhanced the phytoplankton production. Asymmetric distribution of changes in SST and Chl a (strong intensity on the right side of the storm track) was observed from the satellite data. The storm-induced nitrate increase estimated from the satellite SST, using a local relationship between nitrate and temperature measurements was about 40% on average along the track of the storm. A numerical model study and climatological nutrient profile showed an increase in mixed-layer depth of 26 m and nitrate increase of about 0.2 μmol L-1 after the storm passage. In addition to altering the physicochemical conditions of the water column, physical forcing by the hurricane also changed the taxonomic composition of phytoplankton. It is inferred that the dominance of diatoms after the storm is a result of the increase in nutrient concentration within the mixed layer due to the wind forcing of the storm. © The Author 2007. Published by Oxford University Press. All rights reserved.